Effects of teacher expectations on the development of verbal creativity in childhood education / Efectos de las expectativas docentes sobre el desarrollo de la creatividad verbal en la educación infantil - Franco Justo, Clemente (Actualidades Investigativas en Educación, 2008)
In this study, we have assessed the effect that teachers’ positive expectations may have on their student’s verbal creativity. To this end, we have worked with an experimental teacher who holds high expectations of the creativity of students, and a control teacher, where this was not the case and whose positive, favourable expectations of pupils were not high. The statistical analyses carried out have showed a significant increase in the verbal creativity variables evaluated (fluency, flexibility and originality) in the experimental group in comparison to the scores of the control group. En este estudio se evaluó el efecto que una expectativa positiva y favorable por parte del docente podía tener sobre los niveles de creatividad verbal de sus estudiantes. Para ello se contó con la participación de un grupo experimental en el cual se trató de implantar una alta expectativa sobre los niveles de creatividad de sus alumnos, y un grupo control donde no se creó dicha expectativa positiva. Los análisis estadísticos realizados mostraron un incremento significativo en el grupo experimental en las diferentes variables de creatividad verbal evaluadas (fluidez, flexibilidad y originalidad), al comparar sus puntuaciones con las del grupo control.